Design and Analysis for the Improvement of Electric Kettle Performance - Mas Ayu, Hassan; Rosdi, Daud (2008)
This paper presents the new design of kettle coil and the analysis of heat transfer rate in order to improve the performance of current electric kettle. The main purpose of this study was to analyze the performance of new coil design and compared it with the current design in order to examine their effects on different parameters of ecological performance such as heating performance and electricity consumption. Mainly, there are three coil designs were proposed and all designs concept is done using Solidworks software. Then, each of the coil designs will be analyzed and simulated using COSMOSFlow Works software. The analysis will be based on the coil geometry and the heat transfer rate of each design due to different design of the electric kettle coil may result in different water heat transfer rate. After all the data were gathered, the comparison between these new coil designs is done and the best design concept is selected. In order to show and prove that improvement in the current electric kettle has been achieved, the comparison between the boiling rate of the selected design coil and the current design is done. As the result, the new concept of coil design is proven to produce better heating performance with the minimum boiling rate of 600 milliliter per minute, which is more economical and about 34% of energy saving compared to current design.